VERU-111 suppresses tumor growth and metastatic phenotypes of cervical cancer cells through the activation of p53 signaling pathway. (1st February 2020) - Kashyap, Vivek K.; Dan, Nirnoy; Chauhan, Neeraj; Wang, Qinghui; Setua, Saini; Nagesh, Prashanth K.B.; Malik, Shabnam; Batra, Vivek; Yallapu, Murali M.; Miller, Duane D.; Li, Wei; Hafeez, Bilal B.; et al.
Abstract: In this study, we investigated the therapeutic efficacy of VERU-111 in vitro and in vivo model systems of cervical cancer. VERU-111 treatment inhibited cell proliferation and, clonogenic potential, induce accumulation of p53 and down regulated the expression of HPV E6/E7 expression in cervical cancer cells. In addition, VERU-111 treatment also decreased the phosphorylation of Jak2 (Tyr1007/1008) and STAT3 at Tyr705 and Ser727. VERU-111 treatment arrested cell cycle in the G2/M phase and modulated cell cycle regulatory proteins (cyclin B1, p21, p34 cdc2 and pcdk1). Moreover, VERU-111 treatment induced apoptosis and modulated the expression of Bid, Bcl-xl, Survivin, Bax, Bcl2 and cleavage in PARP. In functional assays, VERU-111 markedly reduced the migratory and invasive potential of cervical cancer cells via modulations of MMPs. VERU-111 treatment also showed significant (P < 0.05) inhibition of orthotopic xenograft tumor growth in athymic nude mice. Taken together, our results demonstrate the potent anti-cancer efficacy of VERU-111 in experimental cervical cancer models . Thus, VERU-111 can be explored as a promising therapeutic agent for the treatment of cervical cancer. Highlights: HPV E6 and HPV E7 oncoproteins play important roles in tumorigenesis and cervical cancer progression. VERU-111 concomitantly downregulates HPV E6 and E7 expression via the activations of p53. VERU-111 decreased the expression of phosphorylation of Jak2/STAT3 and display p53-mediated apoptosis. VERU-111 exhibits potent anti-tumor activity in in vitro and in vivo orthotopic xenograft mouse model of cervical cancer.